THE EFFECT OF MOTIVATION, WORK DISCIPLINE, AND COMPENSATION ON EMPLOYEE PERFORMANCE OF PT. HERBA UTAMA (PRODUCTION DEPARTMENT OF FOOD PROCESSING DIVISION): The Effect of Motivation, Work Discipline, and Compensation on Employee Performance of PT. HERBA UTAMA - Tri Wahju Wirjawan; Rizki Intan Fauziah (Bajang Institute, 2023)
Employee performance is the most important thing in human resource management because it is one of the factors that determine the success of the company. Employee performance must be improved in order to provide maximum results for the company. The purpose of this study was to determine and analyze the effect of work motivation, discipline and compensation simultaneously on the performance of employees in the food processing division of PT. Herba Utama. Sampling in this study used a saturated sample, with a total sample of 76 respondents. The data analysis technique used is multiple linear regression using SPSS software version 25. Based on the results of the analysis that has been processed, it is found that all the hypotheses proposed are accepted. Motivation, work discipline, and compensation have a positive and significant effect on the performance of employees in the production division of the food processing division at PT. Herba Utama.